Associations between suturing techniques and suture materials with complications of tubularised incised plate urethroplasty: A systematic review and meta-analysis - Irfan Wahyudi; Putu Angga Risky Raharja; Gerhard Reinaldi Situmorang; Arry Rodjani (Elsevier, 2023)
Summary: Introduction: Tubularised incised plate (TIP) urethroplasty has received widespread acceptability for hypospadias repair. Differences in surgical approach might impact the outcome of TIP urethroplasty. This study was performed to examine the associations between suturing techniques and suture materials with complications of TIP urethroplasty. Methods: Following electronic databases: PubMed, ScienceDirect, EMBASE, and Cochrane Library were systematically reviewed for the studies that reported comparisons of interrupted and continuous suturing techniques and comparisons of several suture materials with complication rates during TIP urethroplasty. Risks of bias were evaluated with RoB 2 tool for randomised controlled trials (RCTs) and ROBINS-I tool for comparative non-RCTs. All data were analysed utilising review manager 5.4. Results: Thirteen total studies involving 2,967 patients underwent TIP procedure were included in this study. However only nine studies fulfilled the criteria for quantitative synthesis. In meta-analysis, there was no significant difference of total complications rate amongst interrupted and continuous suturing techniques (OR 0.86; 95% CI: 0.46-1.59). Subgroup analysis for each complications (urethrocutaneous fistula, infection, dehiscence, meatal stenosis, and urethral stricture) were also not statistically different. The utilisation of absorbable synthetic braided suture compared to monofilament sutures did not increase the complications rate of TIP urethroplasty (OR 1.49; 95% CI: 0.83-2.68). No publication bias was observed in the funnel plot. Conclusion: Our meta-analysis showed that suturing techniques and suture materials had no significance on the complications of TIP urethroplasty. The selection of suturing techniques and suture materials should be based on surgeons or centre's local experience.